Experimental and theoretical studies on ytterbium sensitized erbium-doped fiber amplifier - Moghaddam, M.R.A.; Harun, Sulaiman Wadi; Parvizi, Roghaieh; Salleh, Z.S.; Arof, Hamzah; Lokman, Asiah; Ahmad, Harith (Elsevier, 2011)
The performance of a high power erbium-ytterbium doped fiber amplifier (EYDFA) is investigated experimentally and theoretically. The EYDFA provides a flat gain with an output power higher than 23 dBm in the wavelength region from 1541 to 1565 nm using a multimode pumping at 927 nm. In the theoretical analysis, the rate and power propagation equations are solved to examine the effect of fiber length on the bandwidth of the gain spectra. In the C-band region, the small signal gain of the EYDFA varies from 30 to 34 dB with 10 m long erbium-ytterbium doped fiber (EYDF) while the 927 nm pump power is fixed at 3.5 W. It is shown that the calculated output power is in good agreement with the experimental results, verifying the feasibility of our theoretical model. However, the experimental result shows a relatively lower gain compared to the theoretical result due to the spurious reflection in the cavity and the insertion loss of the EYDF which were neglected in our theoretical model.